Neurobiologische Grundlagen von Muskelschmerz - Mense, Siegfried (Der Schmerz, 1999)
Mechanisms in the lesioned muscle: The peripheral mechanism underlying the tenderness and pain during movement of a damaged muscle is the sensitization of muscle nociceptors. Ongoing activity of nociceptors causes spontaneous pain in addition to tenderness. Muscle pain (particularly that originating in myofascial trigger points) is often mislocalized because it is referred to other deep somatic tissues. The development of trigger points is a purely peripheral event, whereas the referral of muscle pain is based on central nervous mechanisms.Mechanisms at the spinal level: The input from muscle nociceptors induces neuroplastic changes in the spinal cord and higher centres of the central nervous system. These changes are associated with an overexcitability of neurones (central sensitization) and contribute to hyperalgesia of patients. Resting activity of spinal neurones (and hence spontaneous pain) is strongly dependent on nitric oxide (NO). A muscle lesion is likely to lead to an inhibition of the homonymous muscle, it can, however, elicit spasm in another muscle.Supraspinal mechanisms: Spinal neurones that mediate muscle pain are subjected to a strong descending inhibitory influence. The inhibitory tracts originate in the mesencephalon and medulla oblongata. A dysfunction of this inhibitory system might be involved in the pathogenesis of fibromyalgia.
Gesehen am 01.09.2017